Conversão substancial do negócio jurídico - Wongtschowski, Vânia (2008)
This is a master s dissertation with the objective of analyzing the conversion of legal transactions, as regulated by section 170 of the Civil Code, as follows: section 170. If however a null legal transaction contains the requirements of another, the latter shall survive if the purpose intended by the parties allows the assumption that they would have wanted it had they foreseen nullity . This section was inspired by paragraph 140 of the German Civil Code, section 393 of the Portuguese Civil Code and section 1424 of the Italian Civil Code, and is based upon the principle of maintenance of legal values, thus seeking to safeguard the relevance of transactional declarations and ensure that legal transactions may achieve their social function. Throughout the work, the author defends the idea that the purpose of the conversion of legal transactions should be perceived through a social and objective perspective, therefore removing the need to seek the internal will of the agents of the legal relationship in order to seek the practical effects that would arise out of the legal transaction were it not invalid or ineffective in an objective manner and on the basis of the transactional declaration. As such, based upon the analysis of the effects that would be achieved by such transaction, it is possible to conceive its conversion, causing the invalid or ineffective legal transaction to be perceived under a new label by means of an act of legal characterization so that effect can be given to such legal transaction. The conversion of legal transactions is consistent with the evolvement of civil law and the so-called socialization and functions of private law to the extent that it seeks to cause legal transactions achieve their social function, thus not frustrating the trust or the fair expectation of the other party or society